Pengaruh Citra Merekdan Kualitas Produk Terhadap Keputusan Pembelian Mobil Toyota Rush Di Samarinda - Padli Padli (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Padli, 2016 Effect of Brand And Product Quality Consumer Car Buying Decision Against Toyota Rush In Samarinda Syarifah guidance of Mrs. and Mrs. Saida.The purpose of this study to determine the effect of brand image and product quality Buying Decision Against Toyota Rush in Samarinda. Basic theory used marketing management by using multiple linear regression analysis with 30 sample The results of this study as follows:Logistic regression formed is Y = 0.220 + 0.386 X1 + 0,544 X2, Coefficient of regression Brand image and quality of the products is positive, meaning that if there is an increase of variable quality brand image and quality of the product will cause an increase in the consumer's decision to buy a Toyota Rush In Samarinda.The correlation value (R) indicates variables brand image and quality of the products have a strong relationship with the consumer's decision, while the coefficient of determination (R2) of 0.817 indicates that the variable of brand image and quality of the product has an effect on the consumer's decision to buy a Toyota Rush In Samarinda (Y) of 81.7% and 18.3% of consumer decisions to buy cars Toyota Rush In Samarinda influenced by other variables not studied.F count F table and significance of 0.000 Î± = 0.05, which means jointly variables brand image and product quality has a significant influence on the consumer's decision to buy a Toyota Rush In SamarindaPartially indicates that the value of the variable t Brand t variable quality of the product means that the variable quality of the product compared to the variable dominant brand image to the consumer decision to buy a Toyota Rush In SamarindaÂ KEYWORDS: Brand Image, Quality Products - Consumer Decision